ラングホブデ雪鳥沢・スカルブスネスきざはし浜の生物活動域での気象要素の特徴について - 工藤, 栄; クドウ, サカエ; 田邊, 優貴子; タナベ, ユキコ; 内田, 雅己; ウチダ, マサキ; 大園, 享司; オオソノ, タカシ; 伊村, 智; イムラ, サトシ; Kudoh, Sakae; Tanabe, Yukiko; et al. (2015)
P(論文) 昭和基地南方の二つの露岩域（ラングホブデ雪鳥沢・スカルブスネスきざはし浜）に自動気象観測装置を設置し，2010年から気象データの連続観測を開始した．2010-2011年の2年間の気象データの日平均値を昭和基地での観測記録と比較したところ，気温や日射の季節・年変動傾向は酷似しているが，年間を通じて南方露岩の方が1-2℃温暖であること，風速は昭和基地の観測値の1/2 程度であること，相対湿度は10% ほど露岩域の方が乾燥していること，日射は観測地の地形的な影響のため太陽高度の低い季節において昭和基地よりも小さな値が記録されることがわかった．日平均気温が0℃以上となる日数は昭和基地では一年あたり1カ月程度であるのに対し，両露岩域ではその倍以上となっており，この間は200W/m2程度の日射があり，弱風環境であることがわかった．昭和基地よりも温暖で静穏な南方露岩域の気象環境が，陸上生物群集の分布や活動に多大な影響を与えている可能性を指摘した． Observations of weather parameters at two ice-free areas (Yukidori Zawa in Langhovde and Kizahashi Hama in Skarvsnes) on the Soya Coast, East Antarctica, had been conducted since 2010 using automatic weather stations (AWSs). By comparing the data obtained from two AWSs with those at Syowa Station (Ongul Islands), we observed a degree of variability in seasonal and annual air temperature and solar radiation. However, throughout the year, both ice-free areas experienced approximately 1-2℃ higher temperatures and 50% lower wind speeds compared with Syowa Station. Relative humidity and solar radiation (which may be influenced by topographic shading) recorded by both AWS, were ～10% lower than those recorded at Syowa Station. In addition, the numbers of days above 0℃ at both sites was nearly twice that at Syowa Station; we recorded ～200 W/m2 of solar radiation and wind speeds of 3-4 m/s. These differences in weather parameters between the Ongul Islands and ice-free areas on the southern Soya Coast potentially affect the activities of terrestrial biota, and might account for the significant differences in vegetation between the two areas. departmental bulletin paper